Structural and durability properties for magnesia alumina silicate concrete. (18th July 2022) - Dhakal, Milap; Scott, Allan N.; Dhakal, Rajesh P.; Clucas, Don
Highlights : MgO-Al2 SiO3 cement concrete can be designed and constructed similar to conventional PC concrete. Structural and durability properties of MgO-Al2 SiO3 cement concrete are similar to those of PC concrete. MgO-Al2 SiO3 demonstrated better transfer of tensile stresses allowing for greater tensile strain. The rebar-concrete bond performance in the MgO- Al2 SiO3 concrete is comparable to that of PC concrete. Abstract: This paper reports on the fresh, structural and durability properties of a Magnesia-Metakaolin (MgO-Mk) based concrete compared with a conventional Portland cement (PC) concrete. Metakaolin, representing the family of aluminosilicate (Al2 SiO3 ) including low-kaolinitic clays, provides a viable option for use in the M−S−H and M−A−S−H binder system. Two representative cementitious formulations of MgO-Mk cement at a single MgO/clay mass ratio with 100% and 70% Al2 SiO3 content were used in the study. In addition to the basic properties of concrete such as strength and density, this paper also presents the result of comprehensive tests undertaken to evaluate the elastic properties and bond performance of the M−S−H concrete using both steel and basalt reinforcing. The results of the current study demonstrate the properties of MgO-Mk-based M−S−H concrete to be comparable with, if not superior to, those of its PC counterpart.